An objective method of determining recovery period and asymptotic period from loudness adaptation - Vidya Hoskote (Journal of All India Institute of Speech and Hearing, 1970)
This study deals with a new obejctive method of measuring recovery from loudness adaptation (objective residual monaural loudness adaptation) and also asymptotic period of loudness adaptation in normal hearing subjects using Hadsen (7,072) electro-acoustic i~pedance bridge.